Assessment of Environmental Pollution on Public Health Status of Communities in Bauchi Metropolis Bauchi State - Muhammad, Salisu Umar; Ahmed Faruk Umar; John Gushit; Anas Babangida; Suleman Ahmed Wan (Balai Publikasi Indonesia, 2025)
The study was to assessing of environmental pollution on public health status of communities in Bauchi Metropolis Bauchi state, on environmental pollution, which includes the contamination of air, water, and soil, has become a critical global concern due to its profound impacts on public health. The study used systematic sampling technique to obtain data and relevant information from the respondents. The study used survey research design adopted a quantitative method because of its appropriateness to the topic under investigation. Its conscious effort to continuously learn about the poor health status and environment in order to improve the social intervention. In this regard health status can be said to be the meeting of the needs of peoples. The results showed a significant between the mean scores for Air pollution (70.997) and their biological factor that can satisfied peoples of Bauchi Metropolis on the element indicator of the biological factor scale [ANOVA (df = 3) =6.115 35.078, P<.0.00]. A majority of peoples about significant value on 001 of the respondents indicated that they were satisfied with the social intervention. This is followed by a percentage of about .723 who also indicated that they liked the friendliness of Air pollution towards them and the 207 of the respondents who are also pleased with the government ability to handle all enquiries. There were a total 306 respondents, making up with their view on environmental pollution and their mind set. All the areas indicated by respondents are areas that need to be looked at closely by environmental if they wish to satisfy their peoples and hence achieve people’s health status.